Предмет: Алгебра,
автор: машаа3
приведи выражение к упрощенному виду
Приложения:
Ответы
Автор ответа:
0
Ответ: 1
По формуле cos(A+B)=cosAcosB-sinAsinB и cos(A-B)=cosAcosB+sinAsinB.
(cosAcosB-sinAsinB+sinAsinB)/(cosAcosB+sinAsinB-sinAsinB)=(cosAcosB)/cosAcosB)=1
По формуле cos(A+B)=cosAcosB-sinAsinB и cos(A-B)=cosAcosB+sinAsinB.
(cosAcosB-sinAsinB+sinAsinB)/(cosAcosB+sinAsinB-sinAsinB)=(cosAcosB)/cosAcosB)=1
Автор ответа:
0
Ухты, доту играешь, если че меня зови
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Другие предметы,
автор: feechkajasmin
Предмет: Литература,
автор: masonstorm471
Предмет: Химия,
автор: amir2233